Perception and Interest of the Muslim Younger Generation in Sharia Stock Investment: A Qualitative Study on Students in Bandar Lampung - Fathul Amin; Ruslaini; Ulil Albab; Elsa Cahyani (LP2M IAIN Palopo, 2026)
This study aims to analyze the perception and interest of the young generation of Muslims, especially students, towards sharia stock investment in Bandar Lampung City. This study uses a qualitative approach with a phenomenological design to understand students' experiences and subjective meanings. Data was collected through in-depth interviews with 30 active students from UIN Raden Intan Lampung, University of Muhammadiyah Lampung, and IIB Darmajaya who were selected using purposive sampling techniques, and analyzed with interactive models through data reduction, data presentation, and conclusion drawn. The results of the study show that students have a positive perception of sharia stocks as investment instruments that are halal, legal, and in accordance with Islamic principles, but have not been fully followed by investment actions. This gap is influenced by limited financial literacy, high risk perception, and lack of practical assistance. Students' investment interests are influenced by internal factors such as religious values, knowledge, and future motivations, as well as external factors such as the academic and social environment.